(untitled) (Studia Politica. Romanian Political Science Review, 2025)
This research examines the mobilization strategies employed by Vetëvendosje, a left-wing political party in Kosovo, as it transitioned from a grassroots anti-establishment movement to a governing party. In the context of socio-economic inequality, democratic instability, and the legacy of post-communism, the study examines how populist mobilization serves as both a political tool and electoral strategy for social movements transitioning into political parties. Thus, it raises the following research questions: What factors enabled Vetëvendosje to maintain institutional legitimacy after its transition? How did populist mobilization influence its ideology and electoral outcomes? Through process tracing and content analysis of party manifestos, the research evaluates the evolution of populist discourse and its impact on electoral performance. By analyzing changes in identity and narrative within Vetëvendosje, this study contributes to broader discussions on social movements and the transformation of left-wing parties in post-communist societies.